A rare cause of acute upper airway obstruction: a case report - Jane Harding; Csaba Dioszeghy (International Journal of Emergency Medicine)
Abstract Background Sudden collapse and fluctuating consciousness in elderly patients has a broad differential diagnosis, yet timely diagnosis can be critical for appropriate management. This case report underscores the importance of considering uncommon etiologies in patients presenting with such nonspecific symptoms. Case presentation An 82-year-old female presented to the Emergency Department following a collapse at home and reduced conscious level associated with episodes of respiratory arrest. Computed Tomography (CT) pulmonary angiography revealed a significantly dilated oesophagus with tracheal compression. Following successful intubation and identification of the dilated oesophagus with tracheal compression, the patient’s condition stabilized and she was later successfully extubated and discharged from hospital. Conclusions This report adds to the literature on uncommon causes of acute respiratory distress and emphasises the importance of maintaining a broad differential diagnosis when evaluating elderly patients presenting with sudden collapse and respiratory symptoms.